Karl Barth's ecclesiology reconsidered - Healy, Nicholas (Scottish journal of theology, 2004)
The essay begins by noting some of the things Karl Barth might have said to defend himself against Stanley Hauerwas's criticisms, in the otherwise largely appreciative discussion in With the Grain of the Universe, of Barth's anthropology and pneumatology and the consequent problems in his ecclesiology. I then discuss some issues that Barth himself might have wanted to raise with regard to Hauerwas's own ecclesiology, especially in reference to its comparative lack of emphasis upon divine action and the difference that makes to an account of the church's witness. I argue that Barth and Hauerwas differ to some degree in their understanding of the gospel and of Christianity, with Hauerwas emphasizing rather more than Barth the necessity and centrality of the church's work in the economy of salvation. Barth, on the other hand, sees the need rather more than Hauerwas of situating the church's activity within a well-rounded account of the work of the Word and the Spirit. I offer some concluding remarks to suggest that this particular aspect of Barth's ecclesiology is worth preserving as an effective way of responding to modernity.